Impact of Different Daily Light Integrals and Carbon Dioxide Concentrations on the Growth, Morphology, and Production Efficiency of Tomato Seedlings - Huber, Brandon M.; Louws, Frank J.; Hernández, Ricardo (Frontiers in Plant Science, 2021)
Indoor growing systems with light-emitting diodes offer advantages for the growth of tomato seedlings through uniform and optimized environmental conditions which increase consistency between plants and growing cycles. CO2 enrichment has been shown to improve the yield of crops. Thus, this research aimed to characterize the effects of varied light intensities and CO2 enrichment on the growth, morphology and production efficiency of tomato seedlings in indoor growing systems. Four tomato cultivars, ‘Florida-47 R’, ‘Rebelski’, ‘Maxifort’, and ‘Shin Cheong Gang’, were subjected to three different daily light integrals (DLIs) of 6.5, 9.7, and 13 mol m-2 d-1 with a percent photon flux ratio of 40 blue:60 red and an end-of-day far-red (EOD-FR) treatment of 5 mmol m−2 d−1. The plants were also subjected to three different CO2 concentrations: 448  32 (400-ambient), 1010  45 (1000), and 1568  129 (1600) μmol mol-1. Temperature was maintained at 24.3 °C  0.48/16.8 °C  1.1 (day/dark) (22.4 °C average) and relative humidity at 52.56  8.2%. Plant density was 1000 plants m-2 until canopy closure. Morphological measurements were conducted daily to observe the growth response over time. In addition, data was collected to quantify the effects of each treatment. The results showed increases in growth rate with increases in the DLI and CO2 concentration. In addition, CO2 enrichment to 1000-1600 μmol mol-1 increased the light use efficiency (gDM mol-1 applied) by 38-44%, and CO2 enrichment to 1600 μmol mol-1 did not result in any additional increase on shoot fresh mass, shoot dry mass, and stem extension. However, the net photosynthetic rate obtained with 1600 μmol mol-1 was 31 and 68% higher than those obtained with 1000 and 400 μmol mol-1, respectively. Furthermore, the comparison of the light and CO2 treatment combinations with the control (13 mol m-2 d-1-400CO2) revealed that the plants subjected to 6.5DLI-1600CO2, 9.7DLI-1000CO2, and 9.7DLI-1600CO2 treatment combinations exhibited the same growth rate as the control plants but with 25-50% less DLI. Furthermore, two treatment combinations (13.0DLI-1000CO2 and 13.0DLI-1600CO2) were associated with the consumption of comparable amount of energy but increased plant growth by 24-33%.